Development of Integrated Interactive Modules Education for Sustainable Development (ESD) Global Warming Material Junior High School Muhammadiyah Pekanbaru - Widodo, Widodo; Purwanto, Hadi; Sholihat, Neng; Jehloh, Nurulhuda; Suryanti, Suryanti (Biosfer: Jurnal Tadris Biologi, 2023)
This study aims to describe the development of ESD integrated interactive modules. The population of this study was grade VII students of SMP Muhammadiyah Pekanbaru with a sample of 35 people who were given learning using ESD integrated interactive modules. The method used is research development (Research and Development) with the ADDIE development model. The instruments used in this study were validation sheets for material experts and media experts to see the feasibility level of interactive modules, practicality test questionnaires and questionnaires of student responses to the use of interactive modules developed. The results showed that the feasibility of interactive modules based on the results of material expert validation was 75.5% with feasible criteria. Meanwhile, the results of media expert validation obtained a percentage of 81.4% with very feasible criteria. The results of the practicality test questionnaire showed a value of 94.6%, which means that it is very practical to use and the student response questionnaire with an average of 89.74% and the category is very interesting.ABSTRAK: Penelitian ini bertujuan dalam upaya mendeskripsikan pengembangan modul interaktif terintegrasi ESD. Populasi penelitian ini adalah peserta didik kelas VII SMP Muhammadiyah  Pekanbaru dengan sampel sebanyak 35 orang yang diberikan pembelajaran menggunakan modul interaktif terintegrasi ESD. Metode yang digunakan yaitu penelitian pengembangan (Research and Development) dengan model pengembangan ADDIE. Instrumen yang digunakan dalam penelitian ini adalah lembar validasi ahli materi dan ahli media untuk melihat tingkat kelayakan modul interaktif, angket uji praktikalitas serta angket respon peserta didik terhadap penggunaan modul interaktif yang dikembangkan. Hasil penelitian menunjukkan bahwa kelayakan modul interaktif berdasarkan hasil validasi ahli materi sebesar 75,5% dengan kriteria layak. Sedangkan hasil validasi ahli media memperolah persentase 81,4% dengan kriteria sangat layak. Hasil angket uji praktikalitas menunjukan nilai 94,6% yang artinya sangat praktis digunakan dan angket respon peserta didik dengan rata-rata 89,74% dan kategori sangat menarik